2011
DOI: 10.3386/w17541
|View full text |Cite
|
Sign up to set email alerts
|

The Trouble with Boys: Social Influences and the Gender Gap in Disruptive Behavior

Abstract: This paper explores the importance of the home and school environments in explaining the gender gap in disruptive behavior. We document large differences in the gender gap across key features of the home environment -boys do especially poorly in broken families. In contrast, we find little impact of the early school environment on non-cognitive gaps. Differences in endowments explain a small part of boys' non-cognitive deficit in single-mother families. More importantly, non-cognitive returns to parental input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
214
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(242 citation statements)
references
References 5 publications
27
214
0
1
Order By: Relevance
“…If the skill development of boys is affected more by father absence or family disadvantage than the skill development of girls, then changes in the living arrangements of children over time may play a role in the growing education gender gap. Bertrand and Pan (2013) provide supportive empirical evidence, showing that living with a single mother or a young mother has a much larger effect on externalizing behavior and school suspensions for boys than for girls. They interpret the negative behavioral impact of father absence and young mothers as evidence that the non-cognitive skills development of boys is particularly sensitive to family disadvantage.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…If the skill development of boys is affected more by father absence or family disadvantage than the skill development of girls, then changes in the living arrangements of children over time may play a role in the growing education gender gap. Bertrand and Pan (2013) provide supportive empirical evidence, showing that living with a single mother or a young mother has a much larger effect on externalizing behavior and school suspensions for boys than for girls. They interpret the negative behavioral impact of father absence and young mothers as evidence that the non-cognitive skills development of boys is particularly sensitive to family disadvantage.…”
mentioning
confidence: 66%
“…Family disadvantage is strongly negatively associated with early social and behavioral skills for both boys and girls, and it has been suggested that trends in family structure, and in particular the increasing prevalence of single parent families, may have a particularly deleterious effect on the skill development of boys (Bertrand and Pan, 2013;Autor and Wasserman, 2013). If exposure to father absence, povery, or poor neighborhoods harm boys more than girls, then changes in the living arrangements of children over time may explain part of the growing gender gap in educational attainment.…”
Section: Introductionmentioning
confidence: 99%
“…Due to differences in labor force participation and educational attainment trends across genders, as well as the fact that boys are more affected by adverse events and environmental factors than girls (Bertrand and Pan 2013;Autor et al 2016), examining the effect of teacher collective bargaining by gender is instructive. We first focus on estimates among men: Panel A of Table 7 shows estimates of equation (1) The labor force effects are similarly larger for men.…”
Section: Estimates By Gendermentioning
confidence: 99%
“…Cahill, 2006), differences in socialisation (see e.g. Bertrand & Pan, 2013) or differences in personality and non-cognitive skills (see e.g. Spinath, 2014) may also cause a differential impact of the G8-reform on girls and boys, because they may differ in their capacity to concentrate on longer school days or to organise their activities within the tighter time schedule, for example.…”
Section: B By Gendermentioning
confidence: 99%